Kemampuan Penalaran Matematis Siswa Kelas VII MTs. Al-Madani dalam Menyelesaikan Soal Cerita Materi Aritmetika Sosial Tahun Pelajaran 2020/2021 - Nurlaili Mursilawati; Sripatmi Sripatmi; Baidowi Baidowi; Nani Kurniati (Griya Journal of Mathematics Education and Application, 2021)
This study aimed to describe mathematical reasoning in solving story problems of social arithmetic material based on the level of ability of grade VII students of MTs. Al-Madani academic year 2020/2021. This study was conducted at Madrasah Tsanawiyah Al-Madani Pelulan, Kuripan sub-district, West Lombok district. The selection of subjects using purposive sampling technique was selected 6 students from grade VII of MTs. Al-Madani, consists of high-ability students, medium-ability students, and low-ability students, 2 students each. Data collection was carried out by using the test method, documentation and interviews, the data analysis technique used was the qualitative data analysis technique proposed by Miles and Huberman, namely: data reduction, data display, and conclusion drawing. Based on the data analysis of the results written tests and interviews with research subjects, the average score of students' mathematical reasoning for high-ability subjects was 31.5, and the average score for medium-ability subjects was 20.5. The average score of mathematical reasoning for low-ability subjects was 10.5. High-ability subjects met the indicators of understanding the problem of performing mathematical manipulation, finding patterns to make generalizations. and draw conclusions. Medium-ability students met the indicators of understanding the problem. perform mathematical manipulations, and check the validity of an argument.. Low-ability subjects only met the indicators of understanding the problem.